Just care: should doctors give priority to patients of low socioeconomic status? - Hurst, S. A. (2009)
Growing data on the socioeconomic determinants of health pose a challenge to analysis and application of fairness in health. In Just health: meeting health needs fairly, Norman Daniels argues for a change in the population end of our thinking about just health. What about clinical care? Given our knowledge of the importance of wealth, education or social status to health, is fairness in medicine served better by continuing to avoid considering our patients’ social status in setting clinical priorities, or by attempting to equalise existing health inequalities by giving priority to the socioeconomically disadvantaged at the point of care? In this article, I argue that doctors should not attempt the latter. Granted, giving priority to low status would go some way towards compensating unjust health inequalities and the impression of being left aside in other social spaces. It would represent reverse discrimination, but could still be justified inasmuch as disadvantaged groups could be identifiable, and as long as the intent was compensation rather than retribution. However, under current circumstances such priority would risk being attributed arbitrarily, would represent a form of medical proselytising, risk leaving the worst-off with less by alienating the powerful, and require teaching doctors to act in strongly counter-cultural ways—possibly at great cost. Crucially, however, we protect both equal health and equal regard by treating all alike: priority to low status would promote the first somewhat, but at the expense of sacrificing the second.